Optimal digital filter with low Jitter for CCD sensor - Becerra, Lucas Martin; Fernández Moroni, Guillermo; Sofo Haro, Miguel Francisco; Chierchie, Fernando; Chavez, Claudio (Institute of Electrical and Electronics Engineers, 2022)
Fil: Becerra, Lucas Martin. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina